2017
DOI: 10.14444/4016
|View full text |Cite
|
Sign up to set email alerts
|

Fortifying the Bone-Implant Interface Part 2: An In Vivo Evaluation of 3D-Printed and TPS-Coated Triangular Implants

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…The authors postulated that the increased ingrowth and osteogenesis around the osteoconductive implant led to greater implant stability and fusion. MacBarb et al supported this finding in a separate ovine model showing that both 3DP and TPS had substantial bone ingrowth and ongrowth [49].…”
Section: Implantsmentioning
confidence: 79%
See 2 more Smart Citations
“…The authors postulated that the increased ingrowth and osteogenesis around the osteoconductive implant led to greater implant stability and fusion. MacBarb et al supported this finding in a separate ovine model showing that both 3DP and TPS had substantial bone ingrowth and ongrowth [49].…”
Section: Implantsmentioning
confidence: 79%
“…Preclinical studies demonstrate the advantages of 3DP titanium cages, leading to increased bony ingrowth, decreased subsidence, and better imaging characteristics [49]. 3DP also has more precise control of the size, shape, angle, uniformity, and extent of the pores compared to traditional subtractive manufacturing or titanium plasma spray (TPS) coating.…”
Section: Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that AM implants displayed significantly more bony ingrowth into the device's core versus superficial ingrowth with the TPS coated implant. Authors suggest the increased porosity of AM implants more closely mimics native bone and may enhance the biomechanical stability in MIS SI joint fusion [ 32 ].…”
Section: Implantsmentioning
confidence: 99%
“…In addition to its uses to develop custom, patient-specific implants, 3DP technology is also being used to optimize the geometric properties of premade “Off-the-Shelf” (OTS) implants [ 37 ]. As described previously by McGilvray et al, the customizable porosity and stiffness of 3DP materials can more closely mimic native bone and facilitate bony ingrowth [ 30 32 ]. OTS products are created by premanufacturing implants with a wide variety of sizes and fits, thus reducing the additional time required for additional imaging studies and custom implant printing [ 37 ].…”
Section: Implantsmentioning
confidence: 99%